The effective phase of soft RF pulses - Hennel, Franciszek (Concepts in magnetic resonance. Part A, Bridging education and research, 2014)
In this article, the seemingly trivial relation between the spin nutation phase and the phase of radiofrequency (RF) pulses used in NMR is discussed, which in the case of soft (selective) pulses appears more subtle. Unlike hard pulses applied at a common carrier frequency, soft pulses usually have different frequency offsets in the same sequence and their nutation phase cannot be directly linked with the RF phase shift, as the phase shift has no absolute meaning for waves of different frequency. The problem is further complicated in MRI, where RF pulses are accompanied by a time‐dependent slice selection field gradient leading to surprising effects, for example, when two consecutive pulses of identical frequency and phase rotate the spins around different axes depending on slice position. A rule is described that lets the effective nutation phase be derived from the time course the RF phase. Ways to control this time course using various options of digital synthesis are presented. The discussion is illustrated by two popular MRI sequences—fast spin echo (RARE) and balanced steady‐state free precession (true FISP)—whose phase sensitivity easily leads to a pitfall when the frequency synthesis is not programmed with sufficient care. © 2015 Wiley Periodicals, Inc. Concepts Magn Reson Part A 43A: 127–137, 2015.